Effect of growing conditions in the agricultural risk zone on the quality of beet roots during storage - V. I. Filippov; A. O. Zaborskaya (Новые технологии, 2017)
Treatment of table beet root of Bordeaux 237 variety with Biostim growth stimulator when growing in severe climatic conditions of the zone of agricultural risk of Russia increases its yield by 28.9% and the quality indexes by 7.5-20.7% compared to beets grown without treatment. During six months of refrigerated storage, the loss of quality and weight of the beet treated and not treated with the preparation did not exceed 6-8%.